Role of IQ Motif-Containing GTPase-Activating Proteins in Hepatocellular Carcinoma - Dai, Qingqing; Ain, Quratul; Rooney, Michael; Song, Fei; Zipprich, Alexander (Frontiers in Oncology, 2022)
IQ motif-containing GTPase-activating proteins (IQGAPs) are a class of scaffolding proteins, including IQGAP1, IQGAP2, and IQGAP3, which govern multiple cellular activities by facilitating cytoskeletal remodeling and cellular signal transduction. The role of IQGAPs in cancer initiation and progression has received increasing attention in recent years, especially in hepatocellular carcinoma (HCC), where the aberrant expression of IQGAPs is closely related to patient prognosis. IQGAP1 and 3 are upregulated and are considered oncogenes in HCC, while IQGAP2 is downregulated and functions as a tumor suppressor. This review details the three IQGAP isoforms and their respective structures. The expression and role of each protein in different liver diseases and mainly in HCC, as well as the underlying mechanisms, are also presented. This review also provides a reference for further studies on IQGAPs in HCC.